A case of check-rein deformities of the great and lesser toes treated through exploration at the midfoot. Issue 1 (March 2015) - Sinnett, T.; Rudge, B.; Clark, C.
Abstract We present the case of a twenty-two year old man who presented to the orthopaedic clinic complaining of clawing of his great toe. Further examination revealed clawing of the lesser toes and surgical scaring to the fibula and tibia. A history of previous operative fixation for lower limb trauma was described. Exploration of the flexor hallucis longus (FHL) and flexor digitorum longus (FDL) tendons was performed at the level of the midfoot. A full correction was achieved after release of the inter-tendinous connection between FHL and FDL tendons and z-plasty of the FHL tendon. This case highlights another possible complication of tibial fracture which should be actively looked for in patients with this injury. We describe and illustrate the ease of surgical correction through an operative field free of scar tissue which has the ability to possibly prevent unnecessary tendon z-plasty. We suggest that exploration at the midfoot should be the primary surgical intervention in similar cases of check-rein deformity.